Quebra de dormência e métodos de destanização de caquizeiro 'Rama Forte' no Vale do São Francisco - Silva-Matos, Raissa Rachel Salustriano da (2016)
The region São Francisco Valley (Petrolina-PE / Juazeiro-BA), stands out as one of the largest fruit poles in Brazil, mainly of mango and grape production, however the diversification of farming in the region has become essential to meet this demand research on species of humid tropical climate, subtropical and temperate, with economic potential they see being studied in irrigated areas of the Brazilian semiarid. The persimmon is a major opportunity for the region by the good climate adaptability and hardiness. The present study aimed to evaluate the performance of hydrogen cyanamide on dormancy breaking of gems, phenology, production and quality of persimmon fruit in Petrolina-PE, Brazil, as well as checking low-cost methods and that require little technological apparatus for removal astringency that influences the quality of persimmon fruit „Rama Forte‟ produced in the São Francisco Valley. The study was conducted in Petrolina, Pernambuco, Brazil. For the experiment with a randomized complete block design with five treatments to hydrogen cyanamide base (CH) associated with 3.0 % mineral oil: I - control (without application); II - CH to 0.4 %; III - CH to 0.8 %; IV - CH to 1.0 %; and V - CH to 1.5 %; with 5 replications and 5 plants per plot. The parameters evaluated were: duration of phenological stages; total duration of the phenological cycle; percentage of gems of each phase; budding at 30 and 60 days after treatment application; fruit set; number of fruits per plant; average fruit weight; production of fruits per plant; productivity; transversal and longitudinal diameter; firmness; soluble solids; titratable acidity; total extractable polyphenols; total and soluble pectin; and soluble tannins. In addition an astringency experiment with factorial arrangement of 2 x 9, corresponding to two evaluation periods (24 and 48 hours) and nine methods (not removing astringency [out of box]; not removing astringency [in box]; ethanol; CO2 15 %, CO2 20 %; ethephon 150 mg L-1; ethephon 200 mg L-1; ethephon 250 mg L-1; and ethephon 300 mg L-1), which was evaluated: mass loss; firmness; soluble solids; titratable acidity; total extractable polyphenols; total and soluble pectin; and soluble tannins. The results of all phenological variables, budding and production studied responded to doses of hydrogen cyanamide (CH). The persimmon plant „Rama Forte‟ without application of CH spring, but production is insufficient. The phenological cycle is 240 days in untreated plants and plants treated for 205 days with CH. The fruits have quality to commercialization, however present soluble solids and titratable acidity values above the ideal value for consumption. Applying CH no effect on total extractable polyphenols, pectin soluble and full, and tannins in fruits. So we recommend a dose close to 0.8% of CH. To the process of astringency recommend the use of ethanol vapor at low cost, and an input for easy access, and for introducing the smaller soluble tannin levels and confer good firmness of the fruit.